2019
DOI: 10.1186/s12931-019-1252-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Toll-like receptor 7 (TLR7) agonist, AZD8848, on allergen-induced responses in patients with mild asthma: a double-blind, randomised, parallel-group study

Abstract: BackgroundAlthough allergic asthma is a complex area with many interacting factors involved, the ‘hygiene hypothesis’ proposes that a lack of exposure to infection during childhood may polarise the immune system towards allergen-reactive Th2-type responses in genetically susceptible individuals. Toll-like receptors (TLRs) play a key role within the innate immune system and TLR7 agonists have previously been shown to up-regulate Th1 responses and down-regulate Th2 responses to allergens in murine models of alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 48 publications
0
19
1
Order By: Relevance
“…The absence of an anti-T2 effect and impact on the late asthmatic response in this study contrast with those of previous studies with GSK2245035 in allergic rhinitis by Ellis et al [ 13 ], and those by Leaker et al, assessing AZD8848 (another TLR7 agonist) in allergic asthma [ 20 , 24 ]. In the study by Ellis et al, a reduction of total nasal symptoms in response to nasal allergen challenge, and nasal allergic biomarker analyses, revealed trends supporting a response to GSK2245035, with reductions in T2-related cytokines [ 13 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The absence of an anti-T2 effect and impact on the late asthmatic response in this study contrast with those of previous studies with GSK2245035 in allergic rhinitis by Ellis et al [ 13 ], and those by Leaker et al, assessing AZD8848 (another TLR7 agonist) in allergic asthma [ 20 , 24 ]. In the study by Ellis et al, a reduction of total nasal symptoms in response to nasal allergen challenge, and nasal allergic biomarker analyses, revealed trends supporting a response to GSK2245035, with reductions in T2-related cytokines [ 13 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In the study by Ellis et al, a reduction of total nasal symptoms in response to nasal allergen challenge, and nasal allergic biomarker analyses, revealed trends supporting a response to GSK2245035, with reductions in T2-related cytokines [ 13 ]. Leaker et al, found that, compared with placebo, intranasal AZD8848 attenuated the late asthmatic response by approximately 27% at 1 week after dosing, but the results were not sustained at 4 weeks after dosing; however, AZD8848 had no significant effect on eosinophil counts or T2 cytokines [ 20 , 24 ]. TNSS score was evaluated daily, and although some nasal inflammatory mediators were impacted by GSK2245035, no clinically relevant treatment effect on TNSS was observed; however, this finding should be interpreted with caution given that a minimal TNSS score at study enrollment was not mandated (unlike the study by Ellis et al [ 13 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic interferon production and induction of flu-like symptoms were observed, potentially limiting the utility of the compound ( 147 ). A further trial has shown that while drug-related adverse events were frequent, they were mild and well-tolerated ( 148 ). The TLR7 agonist AZD8848 was shown to suppress the allergen-induced late-phase asthmatic response in an RDBPCT where participants were administered AZD8848 intranasally once-weekly for eight weeks.…”
Section: Intracellular Tlrsmentioning
confidence: 99%
“…The exposure to environment and microbes can help to form the growing immunity system and protect subsequent immune-mediated diseases [32]. "Unhygienic exposure" to microorganisms in an early age can prevent the development of allergic diseases in later years [33]. H. pylori infection usually occurs in children, and the way to be infected is related to unhygienic family environment or habits, and this association appears in mouse asthma models [34].…”
Section: Possible Protective Mechanisms Of H Pylori Against Allergicmentioning
confidence: 99%